2021
DOI: 10.1007/s10198-021-01329-6
|View full text |Cite
|
Sign up to set email alerts
|

Complements or substitutes? Associations between volumes of care provided in the community and hospitals

Abstract: Policymakers often suggest that expansion of care in community settings may ease increasing pressures on hospital services. Substitution may lower overall health system costs, but complementarity due to previously unidentified needs might raise them. We used new national data on community and primary medical care services in England to undertake system-level analyses of whether activity in the community acts as a complement or a substitute for activity provided in hospitals. We used two-way fixed effects regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, in our model, we did not find significant associations between increases in primary healthcare physician volume and reductions in public hospital inpatient admissions or outpatient expenses, either before or after the national policy was implemented. Our findings are consistent with those of a previous study in the UK, where increases in primary healthcare services were not associated with reduced hospital activity or expenditure 25. It should be noted that the UK has a strict gatekeeping system that requires referral from primary healthcare facilities in order to obtain hospital care.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, in our model, we did not find significant associations between increases in primary healthcare physician volume and reductions in public hospital inpatient admissions or outpatient expenses, either before or after the national policy was implemented. Our findings are consistent with those of a previous study in the UK, where increases in primary healthcare services were not associated with reduced hospital activity or expenditure 25. It should be noted that the UK has a strict gatekeeping system that requires referral from primary healthcare facilities in order to obtain hospital care.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies in developed countries, such as the UK and Australia, as well as studies in China, have shown that increasing access to primary healthcare services is associated with reduced hospital outpatient visits and inpatient admissions. [24][25][26][27][28] However, evidence on the association between physician staffing improvement and hospital utilisation after China facilitated the establishment of the hierarchical medical system is still lacking.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations